Is Latin America Overcoming its Fear of Floating? - IBARRA,CARLOS A (Instituto de Economía, Pontificia Universidad Católica de Chile, 2007)
This paper analyzes the evolution of fear of floating (FOF) and its effect on output in Colombia and Mexico. It shows that there has been a gradual rise in exchange-rate volatility as the period of floating lengthens in each country. The paper analyzes the implications of this evolution for the behavior of output. It finds that the reduction of FOF has tended to decrease output volatility in Chile. However, the opposite phenomenon has happened in Mexico, while the results for Colombia are ambiguous